Pengaruh Kompetensi, Independensi, Due Professional Care, Akuntabilitas, Time Budget Pressure Dan Kepatuhan Pada Kode Etik Terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik Di Solo Dan Yogyakarta) - Narendra, Galih, Dr. Triyono, SE, M.Si (2015)
This study aimed to analyze the impact of competence, independence, due professional care, accountability, time budget pressure and compliance with the code of ethics on audit quality. The study is to examine auditors of CPA firms in Solo and Yogyakarta with requirements that have worked as an auditor at least one year and have accomplished audit task at least two years. Analysis data method used on this research that includes data quality of validity test and reliability test, the classic assumption test, which consists of normality test, multicollinearity, and heteroscedasticity test, the hypothesis test that includes multiple regression analysis test, accuracy of the model test, statistical tests, and detrminasi coefficient R² test. Based from research in 7 CPA firms in Solo and Yogyakarta had obtained samples that can be processed by 61 respondents. Based on the analysis of data that using multiple linear regression analysis test can be concluded that competence, independence, due professional care, accountability and compliance with the code of ethics have positive effect on audit quality, whereas time budget pressure has negative effect on audit quality. Keywords: competence, independence, due professional care, accountability, time budget pressure, compliance with the code of ethics and audit quality